AESTHETICS AS PHILOSOPHICAL AND ANTHROPOLOGICAL KNOWLEDGE - Скальська, Д. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Modern aesthetics represents a kind of unity that consolidates the philosophy of culture, historical and social anthropology. The term “aesthetic” is a kind of a metalanguage of culture, the so-called “active body” of human civilization that is in the condition of a permanent anthropological crisis, and thus confirming the author’s idea of the necessity to create an “aesthetical anthropology” project.